2019
DOI: 10.3390/condmat4010005
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint Oxygen Redox Reactions in Batteries through High-Efficiency Mapping of Resonant Inelastic X-ray Scattering

Abstract: Realizing reversible reduction-oxidation (Redox) reactions of lattice oxygen in batteries is a promising way to improve the energy and power density. However, conventional oxygen absorption spectroscopy fails to distinguish the critical oxygen chemistry in oxide-based battery electrodes. Therefore, high-efficiency full-range mapping of resonant inelastic X-ray scattering (mRIXS) has been developed as a reliable probe of oxygen redox reactions. Here, based on mRIXS results collected from a series of Li1.17Ni0.2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 27 publications
2
85
2
Order By: Relevance
“…With the ability to detect oxidized oxygen at a specific emission energy that is different from where the TM‐O hybridization signals dominate, [ 12 ] O‐K mRIXS has been recognized as the most direct and reliable spectroscopic tool to fingerprint O redox reaction in oxide electrodes. [ 9,12b,13 ] Specifically, oxidized oxygen in the lattice was found to typically display fingerprint features around 523.7 and 531 eV in emission and excitation energies in mRIXS, respectively. Unlike the conventional O‐K XAS, such features from the oxidized oxygen are easily distinguished from the stronger and broader TM‐O hybridization signals around 525 eV emission energy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the ability to detect oxidized oxygen at a specific emission energy that is different from where the TM‐O hybridization signals dominate, [ 12 ] O‐K mRIXS has been recognized as the most direct and reliable spectroscopic tool to fingerprint O redox reaction in oxide electrodes. [ 9,12b,13 ] Specifically, oxidized oxygen in the lattice was found to typically display fingerprint features around 523.7 and 531 eV in emission and excitation energies in mRIXS, respectively. Unlike the conventional O‐K XAS, such features from the oxidized oxygen are easily distinguished from the stronger and broader TM‐O hybridization signals around 525 eV emission energy.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the conventional O‐K XAS, such features from the oxidized oxygen are easily distinguished from the stronger and broader TM‐O hybridization signals around 525 eV emission energy. [ 13 ] Recent studies have demonstrated detailed analysis of these specific mRIXS features and correlated them to the reversibility and cyclability of oxygen redox in electrode materials. [ 9,12b ] Here, O‐K mRIXS collected on LNMO and LTMO at the pristine state (P) as well as after various cycling, including 1st charged and discharged (1Ch and 1D), 5Ch and 5D, 50Ch and 50D are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each electrode was re-checked on their potential before experiments to make sure their charged states were sustained (see the method section in Supplementary Information). We performed a comprehensive experimental study and analysis of both the cationic redox activities, i.e., the evolution of Ni and Mn valence states, [39][40][41][42] and the ORR activities through O-K mRIXS 23,43,44 . Our results show quantitatively, self-consistently, and unambiguously that NNMO system is a strong ORR system with negligible voltage hysteresis and high initial cycle Coulombic efficiency.…”
Section: Toc Graphicsmentioning
confidence: 99%
“…Thermally activated oxygen redox chemistry in the bulk of LMR at ~100 o C. Since the valence state of TMs in the bulk of the LMR material demonstrates no change at ~100 o C, the oxygen evolution, which has been identified as a key player in the LMR system, becomes the next focus in our search for the charge compensation mechanism for the thermally-driven surface TMs reduction. The oxygen RIXS features have been thoroughly studied and indexed in previous literature 1, 2,29,30 . In particular, the oxygen RIXS feature at an excitation energy (i.e., incident photon) of ~531 eV and emission energy (emitted photon) of ~523 eV is broadly observed and is attributed to the oxygen redox activities.…”
Section: The Redox Activity Of Tms In the Bulk Of Lmr At ~100 O Cmentioning
confidence: 99%